FORMATION AND ANALYSIS OF ECG SIGNALS WITH PATHOLOGIES - Аhadzhanian A. R.; Loza, K. I.; Narimanova, O. V. (Radio Electronics, Computer Science, Control, 2017)
Context. The work is devoted to the actual problem of the generation of electrocardiogram signals with distortions corresponding to the different pathologies. These signals can be used as a standard for developing new and verification of existing methods for biomedical signals analyzing aimed at the diagnosis of heart diseases. Objective. The aim of this work is the formation of electrocardiogram signals with the known types of distortions corresponding to the common pathologies. The formation of electrocardiogram signals with pathologies is carried out in accordance with heart disease «myocardial infarction» as it is the most widespread among all the heart diseases which can be lethal. Method. The description of a set of diagnostic disease symptoms for elements of electrocardiogram signal depending on the type of infarction (subendocardial or transmural) and its stage is studied. To generate the electrocardiogram signals with the given pathologies the modeling using an offset, shift, scale or exception in the time domain of allocated signal component of the normal electrocardiogram is conducted. The time-frequency analysis methods (continuous wavelet transform with the maternal function «Mexican hat» and wavelet transform with the wavelet function «bior1.5») are used for electrocardiogram component detection and determination of their parameters. Results. It came possible to generate electrocardiogram signals both without and with pathologies in the forms of subendocardial and transmural myocardial infarction. Based on the time-frequency analysis of the obtained electrocardiograms it came possible to determine the features of artificially generated signals corresponding to the pledged pathologies. Conclusions (scientific novelty and practical significance). The problem of synthetic formation of an electrocardiogram signal containing deviations from the norm in accordance with the pathologies «subendocardial infarction» and «transmural infarction» is resolved. As a result of the subsequent studies of the received signals with pathologies the method of analysis of electrocardiograms based on wavelet transform is further developed. Recommendations for the use of this method to detect the pathologies in the forms of subendocardial and transmural myocardial infarctions are given. The results of this work are planed to be used in the future to develop electrocardiograms analysis methods for early detection of known cardiac pathologies.